Understanding Local Perceptions of the Drivers/Pressures on the Coastal Marine Environment in Palawan, Philippines - Madarcos, John Roderick V.; Creencia, Lota A.; Roberts, Bethany R.; White, Mathew P.; Nayoan, Johana; Morrissey, Karyn; Fleming, Lora E. (Frontiers in Marine Science, 2021)
The Philippines, as a tropical archipelagic country, is particularly vulnerable to environmental changes affecting coastal and marine settings. However, there are limited studies investigating how these changes are perceived by the local populations who depend directly on the marine environment for their livelihoods, health, and well-being, and who are the most vulnerable to such changes. To explore these issues, we conducted an in-home face-to-face structured survey in 10 coastal communities in Palawan, Philippines (n = 431). As part of the survey, respondents were asked to comment on how important they believed a list of 22 drivers/pressures (e.g., ‘land-use change’) were in affecting their local marine environment. Statistical analysis of this list using Exploratory Factor Analysis suggested the 22 drivers/pressures could be categorized into 7 discrete groups (or in statistical terms ‘factors’) of drivers/pressures (e.g., ‘urbanization’, ‘unsustainable fishing practices’ etc.). We then used ordinary least squared regression to identify similarities and differences between the perspectives within and across communities, using various socio-demographic variables. Results suggested that among the seven identified factors, four were perceived by the local communities as making the marine environment worse, two were perceived as having no impact, and one was perceived to be making the marine environment better. Perceptions differed by gender, education, ethnicity, and study site. A subsequent survey with 16 local coastal resource management experts, suggested that public perceptions of the most critical drivers/pressures were broadly consistent with those of this expert group. Our findings highlight how aware local coastal communities are of the drivers/pressures underpinning the threats facing their livelihoods, health, and well-being. Ultimately, this information can support and inform decisions for the management of local marine resources.